Knowledge and the attitude of the nurses in Imam Khomeini Complex Hospital about pre and post-death cares - Vasegh Rahimparvar F; Noghani F (Tehran University of Medical Sciences, 2004)
Introduction: Death of a patient is an unavoidable stage of nursing and in many cases nurse is the only person who takes care of the patient at the time of death. An experienced and committed nurse obliges her/himself to care for the patient before and after death in the best way possible. Materials and Methods: This research is a descriptive study that carried out in order to determine knowledge and attitude of the nurses about pre and post-death cares. The samples were 227 nurses of Imam Khomeini Complex Hospital. The number of subjects chosen from each hospital was proportional to the number of nurses of that hospital. The samples were selected randomly. Data were collected by a questionnaire, validity of which was confirmed by content validity and reliability of it was confirmed by test-retest method. Data were analyzed with descriptive statistics. Results: Results showed that in majority of the nurses level of knowledge about pre-death cares was moderate and was poor about post-death cares. The majority of the nurses had a positive attitude about pre-death cares and a relatively positive attitude about post-death cares. There was not any sample with negative attitude about pre or post-death cares. Conclusion: Regarding the undesirable level of knowledge and positive attitude of the nurses under study concerning pre and post-death cares and considering that the necessity for improving the knowledge is training and education, the results of this research can help authorities to provide training and educational programs for enhancing nurses' knowledge regarding pre- and post-death cares.